2003
DOI: 10.2174/0929867033368583
|View full text |Cite
|
Sign up to set email alerts
|

Synergy in Plant Medicines

Abstract: The notion that medicines derived from plants depend for their action on active principles present has to be modified in view of the findings that there are, in many cases, adjuvant substances in the plant which enhance the activity of the components actually responsible for the effect. This synergy may involve protection of an active substance from degradation by enzymes; it may facilitate transport across barriers such as cell and organelle walls, it may overcome multi-drug resistance mechanisms or provide o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(86 citation statements)
references
References 0 publications
0
83
0
3
Order By: Relevance
“…This practice may produce synergistic or antagonistic effects (Gilbert & Alves, 2003;Rodrigues & Carlini, 2004).…”
Section: Few Ethnopharmacological Surveys Amongmentioning
confidence: 99%
“…This practice may produce synergistic or antagonistic effects (Gilbert & Alves, 2003;Rodrigues & Carlini, 2004).…”
Section: Few Ethnopharmacological Surveys Amongmentioning
confidence: 99%
“…Broad-spectrum inhibitory potential of plant extracts and biocompounds from natural sources against bacteria have been reported [48][49][50][51], and efflux pump inhibitors such as 5 -methoxyhydnocarpin isolated from Berberis fremontii which inhibited NorA efflux pump in Staphylococcus aureus, have been found to enhance antibacterial properties of other antibacterial agents [23,43]. These efflux pump inhibitors if actually present in the n-hexane fraction used in this study (further work is ongoing on this) may have broad-spectrum activity considering the fact that synergy observed was non-specific to either Gram-positive or -negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of antimicrobial combination therapy involving biomolecules could include treatment of mixed infections, therapy for acute and critical infections caused by known etiological agents, augmentation of antibacterial activities, reduction of the time needed for developing long-term antimicrobial agents and prevention of resistant microbes [21,22]. Furthermore, this kind of therapy may involve protection of an active substance from degradation by enzymes, facilitate transport across barriers such as cell and organelle walls, overcome multidrug-resistance mechanisms or provide other signals to the host's cells that result in higher efficacy of the crude drug when combined with a synthetic drug [23]. Although combination therapy has been reported to be beneficial, there is a need to investigate a combination of antimicrobial agents that will yield synergism, indifference or antagonism.…”
Section: Introductionmentioning
confidence: 99%
“…Specially, since there was mounting evidence which demonstrated that medicinal plants contained synergistic and/or side-effect neutralizing combinations (Thyagarajan et al, 2007;Gilani and Rahman, 2005). In contrast to synthetic pharmaceuticals based upon single chemicals, phytomedicines exert their beneficial effects through the additive or synergistic action of their multitude of constituents acting at single or multiple target sites (Dalby-Brown et al, 2005); because of their primary and secondary metabolite roles (Greenspan et al, 1994) and the adjuvant substances which enhance the activity of components actually responsible for the effect (Gilbert et al, 2003). In order to take the maximum advantage of the therapeutic properties as well as benefits of the synergistic action of the active principles in medicinal plants, it is necessary to use herbal combinations.…”
Section: Circulat´s Therapeutic Properties In Diabetic Foot: Synthesismentioning
confidence: 99%